Architectural Design Of Enterprise At Madrasah I’dadiyah Sukorejo Using Togaf ADM - Ahmad Efendi; ALI Muhajir (Diagnosa, 2025)
The rapid development of information technology has encouraged educational institutions to transform their management systems into integrated digital systems. Madrasah I’dadiyah Sukorejo still relies on manual and separated information management, which affects efficiency, data accuracy, and decision-making processes.This study aims to design an enterprise architecture model as a guideline for developing an integrated information system at Madrasah I’dadiyah Sukorejo using the TOGAF ADM framework.This research applies a qualitative descriptive approach by adopting the TOGAF Architecture Development Method (ADM). Data were collected through direct observation, interviews with school management and teachers, and document analysis. The architectural design was developed through several TOGAF ADM phases, including architecture vision, business architecture, application architecture, data architecture, and technology architecture.The results of this study produce an enterprise architecture blueprint that maps core and supporting business processes, recommends nineteen integrated application systems, and proposes a centralized technology infrastructure supported by secure network architecture. This design aligns information systems with institutional goals and improves efficiency, integration, and service quality. The proposed enterprise architecture design provides a strategic foundation for Madrasah I’dadiyah Sukorejo to implement an integrated and sustainable information system, supporting its digital transformation and future development.